Metal deposition by electroless plating on polydopamine functionalized micro- and nanoparticles - Mondin, Giovanni; Wisser, Florian M.; Leifert, Annika; Mohamed-Noriega, Nasser; Grothe, Julia; Doerfler, Susanne; Kaskel, Stefan (Journal of Colloid and Interface Science, 2013)
A novel approach for the fabrication of metal coated micro- and nanoparticles by functionalization with a thin polydopamine layer followed by electroless plating is reported. The particles are initially coated with polydopamine via self-polymerization. The resulting polydopamine coated particles have a surface rich in catechols and amino groups, resulting in a high affinity toward metal ions. Thus, they provide an effective platform for selective electroless metal deposition without further activation and sensitization steps. The combination of a polydopamine-based functionalization with electroless plating ensures a simple, scalable, and cost-effective metal coating strategy. Silver-plated tungsten carbide microparticles, copper-plated tungsten carbide microparticles, and copper-plated alumina nanoparticles were successfully fabricated, showing also the high versatility of the method, since the polymerization of dopamine leads to the formation of an adherent polydopamine layer on the surface of particles of any material and size. The metal coated particles produced with this process are particularly well suited for the production of metal matrix composites, since the metal coating increases the wettability of the particles by the metal, promoting their integration within the matrix. Such composite materials are used in a variety of applications including electrical contacts, components for the automotive industries, magnets, and electromagnetic interference shielding. © 2013 Elsevier Inc.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Al; Copper; Electroless plating; Metal matrix composites; Nanoparticles; Polydopamine; Silver; WC